KORELASI MINAT BACA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 TANJUNGPINANG - Suryani, Shelly; Pujiastuti, Indah; Elfitra, Legi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is one of the essential language skills that supports students' academic achievement. However, differences in students' reading interest may influence their ability to comprehend descriptive texts. This study aimed to determine the relationship between reading interest and descriptive text reading comprehension skills among seventh-grade students at SMP Negeri 2 Tanjungpinang for the 2025/2026 academic year. This research employed a quantitative correlational approach. The population consisted of 271 seventh-grade students, with a sample of 54 students selected through simple random sampling. Data were collected using a reading interest questionnaire and a descriptive text reading comprehension test. The collected data were analyzed using descriptive statistics and Pearson Product Moment correlation with the assistance of IBM SPSS Statistics. The findings revealed that students' reading interest was generally categorized as good, while their descriptive text reading comprehension skills were also in the good category. Nevertheless, the correlation analysis indicated no significant relationship between reading interest and descriptive text reading comprehension skills. These findings suggest that students' reading comprehension is influenced not only by reading interest but also by other factors, such as vocabulary mastery, reading strategies, learning motivation, and the learning environment. Therefore, improving reading comprehension requires comprehensive instructional strategies and continuous literacy programs in schools.